KARAKTERISTIK MINUMAN ISOTONIK AIR KELAPA MUDA DENGAN PENAMBAHAN SARI BUAH KELUBI - Rossy Nurmitha; Usman Pato; Emma Riftyan (Fakultas Pertanian Universitas Riau, 2025)
Isotonic drinks are carbonated or non-carbonated soft drinks that contain sugar, nitric acid, and minerals to improve fitness. Isotonic drinks can be made from young coconut water by adding fruit juice to complement the nutritional content of isotonic drinks. One of the fruits that can be added is kelubi fruit. Kelubi is a fruit of the Araceae family that has complete nutritional content and is rich in organic acids. The purpose of this study was to determine the selected treatment of isotonic drink from coconut water added with kelubi fruit juice with different concentrations. The research was conducted experimentally using a complete randomized design with four treatments and four replications. The treatments in this study were K1 (3%), K2 (8%), K3 (13%), and K4 (18%). Data were analyzed statistically using analysis of variance, and differences between treatments were analyzed using Duncan’s New Multiple Range Test (DNMRT) at the 5% level. The result showed that the concentration of kelubi fruit juice significantly affected sodium content, potassium content, acidity, total acid, total sugar, and sensory assessment of isotonic drinks. The best treatment in this study was K2 (8%) with a sodium content of 412.40 mg/kg, potassium content of 315.40 mg/kg, pH 3.90, total acid 0.58%, total sugar 12.29%, and descriptive sensory assessment of orange color, kelubi scent, and sweet taste and hedonic assessment including color, aroma, and taste, and overall was preferred by the panelists.